The impact of loss on high-Q resonant metasurfaces: A case study for heated a-Si:H. (December 2022) - Barreda, Angela; Kuppadakkath, Athira; Ghazaryan, Lilit; Gan, Ziyang; Koshelev, Kirill; Bucher, Tobias; Pertsch, Thomas; George, Antony; Turchanin, Andrey; Szeghalmi, Adriana; Kivshar, Yuri; Choi, Duk-Yong; et al.
Highlights: The excitation of q-BIC resonances can be useful for enhancing the emission of 2D materials. The robustness of the q-BIC resonances to optical losses in all-dielectric metasurfaces is studied. The Q-factor decreases exponentially with the losses increase. The results are interesting for the design of metasurfaces suitable for growing 2D materials. Abstract: The excitation of quasi bound states in the continuum (q-BIC) resonances has been demonstrated in the last years to be useful for lasing, non-linear effects, sensing, or photoluminescence enhancement. In particular, the usage of q-BIC resonances in all-dielectric hydrogenated amorphous silicon (a-Si:H) metasurfaces for enhancing the light-matter interaction with 2D materials has been recently proposed. Growing 2D material directly on the metasurface requires heating to high temperatures, changing the metasurface optical properties (absorption increase). This fact makes necessary to consider the effect of losses on the excitation of q-BIC resonances. Here, we study the influence of absorption losses on the Q -factor values of an a-Si:H metasurface designed to exhibit a q-BIC resonance in the visible spectral region. As a concrete example, we investigate the consequences of heating the metasurface under investigation. We demonstrate that the increase in the optical losses decreases the Q -factor values or even prevents the excitation of the q-BIC resonance in the metasurface. This work may pave the way for the design of metasurfaces suitable for growing 2D materials directly on the metasurface. This integration scheme can resolve many challenges associated with the present transfer-based method for the coupling of 2D materials to metasurfaces.